2011
DOI: 10.1164/rccm.201012-2033oc
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Preatherosclerotic Remodeling Induced by Intermittent Hypoxia Is Attenuated by RANTES/CCL5 Inhibition

Abstract: Inflammation is a determinant mechanism for IH-induced preatherosclerotic remodeling involving RANTES/CCL5, a key chemokine in atherogenesis. Characterization of the inflammatory response could allow identifying at-risk patients for complications, and its pharmacologic manipulation may represent a potential complementary treatment of sleep apnea consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
102
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 44 publications
9
102
0
3
Order By: Relevance
“…Numerous lines of evidence indicate that oxidative stress affects the vascular tone, on one hand through decreased NO bioavailability contributing to endothelial dysfunction and, on the other hand, by promoting vascular cell proliferation, inflammation, and extracellular matrix remodeling 8. Our results are in accordance with previous studies demonstrating that long‐term exposure to IH induces vascular oxidative stress13, 14 (ie, superoxide anion production) and inflammation10, 11, 12, 44, 46 (ie, NF‐κB, F4/80, CD45, and interferon‐γ expression). In addition, using in vitro transendothelial electrical resistance measurement, we demonstrated that IH also induces endothelial barrier dysfunctions, confirming recent data from Prabhakar's group that demonstrates in endothelial cell cultures a central role of reactive oxygen species in promoting IH‐associated endothelial barrier dysfunctions 47.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Numerous lines of evidence indicate that oxidative stress affects the vascular tone, on one hand through decreased NO bioavailability contributing to endothelial dysfunction and, on the other hand, by promoting vascular cell proliferation, inflammation, and extracellular matrix remodeling 8. Our results are in accordance with previous studies demonstrating that long‐term exposure to IH induces vascular oxidative stress13, 14 (ie, superoxide anion production) and inflammation10, 11, 12, 44, 46 (ie, NF‐κB, F4/80, CD45, and interferon‐γ expression). In addition, using in vitro transendothelial electrical resistance measurement, we demonstrated that IH also induces endothelial barrier dysfunctions, confirming recent data from Prabhakar's group that demonstrates in endothelial cell cultures a central role of reactive oxygen species in promoting IH‐associated endothelial barrier dysfunctions 47.…”
Section: Discussionsupporting
confidence: 92%
“…These data are in accordance with clinical observations, demonstrating a significant increase in the carotid artery intima‐media thickness in patients with OSA that correlates to the severity of nocturnal hypoxemia 38, 39, 41. In rodent models, exposure to at least 14 days of IH resulted in enlarged intima‐media thickness and/or disruption of the elastic network 10, 11, 12, 37, 42, 43. In addition to structural remodeling, arterial stiffness and hypertension are also under the control of endothelial‐derived mediators, such as NO,40 and reduced NO bioavailability contributes to endothelial dysfunction, which represents a hallmark of hypertension and arterial stiffening.…”
Section: Discussionsupporting
confidence: 90%
“…Leukocyte-endothelium adhesive interactions were increased, attested by leukocyte rolling and intercellular adhesion molecule (ICAM)-1 expression in mesenteric vessels. Aortas had increased intima media thickness [57]. Systemic inflammation plays a pivotal role in all stages of atherosclerosis in general [58] and hence, not surprisingly, it is also central in intermittent hypoxia-induced pathogenesis.…”
Section: Systemic Inflammationmentioning
confidence: 97%
“…Even in non-genetically modified animals fed with a normal diet, intermittent hypoxia led to early changes including downregulated endothelial Platelet endothelial cell adhesion molecule-1 (a marker of vascular remodelling) expression at the aortic and cardiac levels suggesting endothelial dysfunction or an early event of atherogenesis [56]. ARNAUD et al [57] further evidenced that inflammatory pre-atherosclerotic remodelling was involved since systemic inflammation, as well as structural and inflammatory vascular alterations, occurred after 2 weeks of intermittent hypoxia. Leukocyte-endothelium adhesive interactions were increased, attested by leukocyte rolling and intercellular adhesion molecule (ICAM)-1 expression in mesenteric vessels.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Indeed, a very short-term exposure of only 3 h to experimentally induced obstructive apnoeas in rats can lead to increased leukocyte rolling, reflecting leukocyte-endothelial cell interaction and expression of P-selectin in colonic veinules [107]. We recently found that intermittent hypoxia led to early systemic and vascular inflammatory alterations including splenic T-cell activation, chemokine expression and increased expression of adhesion molecules in small and large arteries, as well as structural remodelling [108].…”
Section: Osa Intermittent Hypoxia and Cardiovascular And Metabolic Cmentioning
confidence: 99%